2013
DOI: 10.3329/jhpn.v31i2.16384
|View full text |Cite
|
Sign up to set email alerts
|

Major Dietary Patterns in Relation to Stunting among Children in Tehran, Iran

Abstract: To the best of our knowledge, no information is available to link major dietary patterns to stunting during childhood, although dietary patterns are associated with chronic diseases. This study was conducted to determine the relationship between major dietary patterns and stunting in the first grade pupils of Tehran in 2009. In this case-control study, 86 stunted children (defined as height-for-age of less than the 5th percentile of CDC2000 cutoff points) were enrolled from among 3,147 first grade pupils of Te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
35
0
12

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 22 publications
10
35
0
12
Order By: Relevance
“…Similar study conducted by Esfarjani et al (2013), find that there is a positive effect and statistically significant of nutrient intake (carbohydrate and protein) toward the risk of stunting on children. The result of the study showed that high carbohydrate and protein intake are related to the reduced risk of stunting on children by 0.31 time (Esfarjani et al, 2013).…”
Section: Methodssupporting
confidence: 60%
See 1 more Smart Citation
“…Similar study conducted by Esfarjani et al (2013), find that there is a positive effect and statistically significant of nutrient intake (carbohydrate and protein) toward the risk of stunting on children. The result of the study showed that high carbohydrate and protein intake are related to the reduced risk of stunting on children by 0.31 time (Esfarjani et al, 2013).…”
Section: Methodssupporting
confidence: 60%
“…The result of the study showed that high carbohydrate and protein intake are related to the reduced risk of stunting on children by 0.31 time (Esfarjani et al, 2013).…”
Section: Methodsmentioning
confidence: 83%
“…Another study conducted, determined the relationship between major dietary patterns and stunting in the first grade students in Tehran, discovered three major dietary patterns. They were identified as: 'traditional dietary pattern', 'mixed dietary pattern' and 'carbohydrate-protein pattern' (17). In the 'traditional dietary pattern' of the mentioned study, eggs, sugars and vegetables were in common with the transitional DP of the present study.…”
Section: Discussionmentioning
confidence: 93%
“…Also results of Esfarjani et al study on 308 grade 1 primary school children in Tehran showed insufficient consumption of vegetables (123 ± 116 g/d), fruits (343 ± 316 g/d), and dairy products (383 ± 232 g/d). They also reported that intake of drinks and fast foods were 243 ± 178 g/d and 201 ± 113 g/d, respectively (24). According to our findings, 68% of the students had medium, 28% good and about 3% low nutritional knowledge.…”
Section: Discussionmentioning
confidence: 58%